PREVALENSI SINDROM KORONER AKUT DI RSUP PROF. DR. R. D. KANDOU MANADO PERIODE 1 JANUARI 2014 - 31 DESEMBER 2014 - Tumade, Biancha; Jim, Edmond L.; Joseph, Victor F. F. (e-CliniC, 2016)
Abstract: Acute Coronary Syndrome (ACS) is a syndrome that occurred due to pathological changes inside the coronary artery wall which cause myocardial ischemic, Unstable Angina Pectoris (UAP), and Acute Myocardial Infarct (AMI) such as Non ST Elevation Myocardial Infarct (NSTEMI) and ST Elevation Myocardial Infarct. The prevalence of coronary heart disease (CHD) in Indonesia is 0.5% from the total sample of non-communicable diseases and from the total sample diagnosed with CHD the highest is in Middle Sulawesi (0.8%) followed by North Sulawesi (0.7%). This study aimed to obtain the prevalence of ACS in Prof. Dr. R. D. Kandou Hospital from 1 January to 31 December 2014. This was a descriptive retrospective study. Data were obtained from the medical record and Cardiovascular and Brain Center (CVBC) of Prof. Dr. R. D. Kandou Hospital in Manado. The results showed that there were 126 cases of ACS, 72 cases (57.1%) of UAP, 35 cases (37.8%) of NSTEMI, and 19 cases (15.1%) of STEMI. From the 126 cases there were 90 males (71.4%) and 36 females (28.6%). Based on age there were 2 cases (1.6%) of 31-40 years old, 15 cases (11.9%) of 41-50 years old, 42 cases (33.3%) of 51-60 years old, 48 cases (38.1%) of 61-70 years old, 16 cases (12.7%) of 71-80 years old, and 3 cases (2.4%) of over 80 years old. Based on histories of ACS assisted diseases, there were 87 (69.0%) cases of hypertension, 32 cases (25.4%) of diabetes mellitus, 37 cases (29.4%) of dyslipidemia, 7 cases (5.6%) of obesity, 19 cases (15.1%) of smokers, and 122 cases (96.8%) of ACS patients had more than one risk factor. Conclusion: In this study, the most prevalence of ACS was UAP, males, aged 61-70 years, and had hypertension history. Keywords: acute coronary syndrome, prevalence Abstrak: Sindrom Koroner Akut (SKA) merupakan keadaan terjadinya perubahan patologis dalam dinding arteri koroner, sehingga menyebabkan iskemik miokardium dan menimbulkan Unstable Angina Pectoris (UAP) serta Infark Miokard Akut (IMA) seperti Non ST Elevation Myocardial Infarct (NSTEMI) dan ST Elevation Myocardial Infarct (STEMI). Di Indonesia prevalensi penyakit jantung koroner (PJK) sebesar 0,5% dari total sampel penyakit tidak menular dan tertinggi di Sulawesi Tengah sebanyak 0,8% diikuti Sulawesi Utara 0,7% dari total pasien terdiagnosis PJK. Penelitian ini bertujuan untuk mengetahui prevalensi penderita SKA yang dirawat di RSUP Prof. Dr. R. D. Kandou Manado periode 1 Januari 2014 sampai 31 Desember 2014. Penelitian ini merupakan studi deskriptif retrospektif dengan menggunakan data Bagian Rekam Medik dan Cardivascular and Brain Center (CVBC) RSUP Prof. Dr. R. D. Kandou Manado. Hasil penelitian memperlihatkan 126 kasus SKA, kasus UAP sebanyak 72 kasus (57,1%), NSTEMI 35 kasus (37,8%), dan STEMI 19 kasus (15,1%). Laki-laki sebanyak 90 kasus (71,4%) dan perempuan 36 kasus (28,6%). Kelompok umur 31-40 tahun sebanyak 2 kasus (1,6%), 41-50 tahun 15 kasus (11,9%), 51-60 tahun 42 kasus (33,3%), 61-70 tahun 48 kasus (38,1%), 71-80 tahun 16 kasus (12,7%), dan >80 tahun 3 kasus (2,4%). Riwayat hipertensi sebanyak 87 kasus (69,0%), diabetes melitus 32 kasus (25,4%), dislipidemia 37 kasus (29,4%), obesitas 7 kasus (5,6%), dan merokok 19 kasus (15,1%). Simpulan: Prevalensi kasus SKA terbanyak adalah kasus UAP, berjenis kelamin laki-laki, berumur 61-70 tahun, serta memiliki riwayat hipertensi.Kata kunci: sindrom koroner akut, prevalensi